2007
DOI: 10.1007/s00210-007-0188-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of verapamil on tachycardia-induced early cellular electrical remodeling in rabbit atrium

Abstract: We investigated the effects of a 7-day verapamil pretreatment (VPT, 7.5 mg/kg bodyweight subcutaneously every 12 h) on ionic currents and molecular mechanisms underlying tachycardia-induced early electrical remodeling after 24-h rapid atrial pacing (RAP, 600 bpm) in rabbit atrium. Animals were divided into four groups (n = 6 each group): control (not paced, no verapamil), paced only, verapamil only and verapamil and paced, respectively. VPT doubled ICa,L [7.0 +/- 0.7 pA/pF (control) vs 14.2 +/- 0.6 pA/pF (vera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
1
2
1
Order By: Relevance
“…Jones et al ( 2000 ) reported a reduction of I K1 current in guinea pig ventricular cardiomyocytes, whereas Waldegger et al ( 1999 ) reported a significant reduction of current produced by Kir2.1 subunits expressed in Xenopus laevis oocytes where other cardiac potassium channels were coexpressed including the potassium channels Kv1.1, Kv1.5, Kir2.1, and HERG, and the IsK subunit of the I Ks -channel complex. Contrary to these findings in a rabbit atrium tachycardia pacing model, no effect of verapamil pretreatment on I K1 was reported by Laszlo et al ( 2007 ). We therefore oriented our study towards the effects of verapamil on all the Kir channel subunits that constitute the cardiac I K1 current (Kir2.1, 2.2, and 2.3).…”
Section: Discussioncontrasting
confidence: 79%
“…Jones et al ( 2000 ) reported a reduction of I K1 current in guinea pig ventricular cardiomyocytes, whereas Waldegger et al ( 1999 ) reported a significant reduction of current produced by Kir2.1 subunits expressed in Xenopus laevis oocytes where other cardiac potassium channels were coexpressed including the potassium channels Kv1.1, Kv1.5, Kir2.1, and HERG, and the IsK subunit of the I Ks -channel complex. Contrary to these findings in a rabbit atrium tachycardia pacing model, no effect of verapamil pretreatment on I K1 was reported by Laszlo et al ( 2007 ). We therefore oriented our study towards the effects of verapamil on all the Kir channel subunits that constitute the cardiac I K1 current (Kir2.1, 2.2, and 2.3).…”
Section: Discussioncontrasting
confidence: 79%
“…As another molecular basis of Ito, Kv4.2 50 shows a stretch-induced downregulation in cultured atrial neonatal myocytes of rats, 51 positive haemodynamic effects of EPT and consequent lowered wall-stress during RAP cannot be excluded as another mechanism for prevention of Ito downregulation by RAP after EPT. Similar to our experiments with verapamil 52 the observation that downregulation of one channel (enalapril: Ito, verapamil: ICa,L) due to RAP can be prevented by medicamental pre-treatment whereas downregulation of the other (enalapril: ICa,L, verapamil: Ito) is not affected, points to different pathways of ICa,L respectively Ito downregulation due to RAP. As the tachypacinginduced downregulation of Ito has complex but relatively small effects on human and canine atrial APD in a mathematical model of an atrial myocyte, 53,54 the functional importance of the prevention of Ito downregulation by EPT cannot be stated at the moment, but insights from these models also showed that absolute impact of Ito on APD in comparison is much more pronounced in the early phases of AF (more 'sinus rhythm-like' action potential) as in chronic AF ('remodelled' action potential), which is in accordance with the already mentioned potential Ang II independence (or indirectly independence of EPT) of AERP-shortening after longer pacing intervals.…”
Section: Transient Outward Potassium Currentsupporting
confidence: 89%
“…Animals were instrumented as previously described in detail (Laszlo et al 2007). Adult female New Zealand white rabbits (weight 2.5 to 3 kg) were anesthetized with ketamine 75 mg/kg and xylazine 5.8 mg/kg with additional doses applied as needed.…”
Section: Instrumentation Of Animalsmentioning
confidence: 99%